THE SPIRITUAL-ECOLOGICAL APPROACHES OF INDIGENOUS COMMUNITIES OF TIDORE TOWARDS ENVIRONMENTAL CONSERVATION - David Efendi; Arifin Muhammad Ade; Alam Mahadika (Jurnal Sosiologi Reflektif, 2022)
G20 summit in August has established various strategies and issues focusing in environmental managements, especially climate change. It has prompted some parties to realize a better understanding of climate change amid their limitations. The roles of indigenous communities are considered by many social scientists as parties which are able to contribute significantly to environmental conservation which indirectly has an impact on corporate efforts as the G20 country aspires to. This study intends to explain how the spiritual beliefs and practices of indigenous peoples in Tidore, North Maluku, who have been acculturated with Islam, can catalyze natural preservation. This research was conducted through an ethnographic approach in Kalaodi village, Tidore, North Maluku. The data was collected through observations and in-depth interviews with 16 informants consisting of traditional leaders, heads of village, and ordinary civilians. The findings showed that the beliefs and eco-spiritual practices of the Kalaodi people, known as Paca Goya, have successful impacts in environmental issues in the region remaining sustainable and even become one of the protected forests in Indonesia. It is undoubtedly a positive approach of campaigning better understanding of climate change amid public confusion about the threat of global warming.Negara G20 pada KTT Agustus lalu telah memantapkan berbagai strategi dan fokus isu dalam pengelolaan lingkungan, khususnya perubahan iklim. Hal ini mendorong sejumlah pihak untuk bagaimana mewujudkan perubahan iklim yang lebih baik di tengah berbagai keterbatasan yang ada? Peran komunitas adat dewasa ini dilirik oleh banyak ilmuwan sosial telah berkontribusi signifikan dalam konservasi lingkungan yang secara tidak langsung tentu memiliki dampak pada upaya peruahan iklim seperti yang dicita-citakan Negara G20. Penelitian ini bermaksud untuk menjelaskan bagaimana keyakinan dan praktik spritual masyarakat adat di Tidore Maluku Utara yang telah berakulturasi dengan budaya Islam mampu menjadi katalisator dalam pelestarian alam. Penelitian ini dilakukan melalui pendekatan etnografi di desa Kalaodi, Tidore, Maluku Utara. Data dikumpulkan melalui observasi dan wawancara mendalam terhadap 16 informan yang terdiri dari tokoh adat, lurah, dan warga. Hasil penelitian menunjukkan bahwa keyakinan dan praktik eco-spiritual masyarakat Kalaodi yang dikenal dengan Paca Goya telah berhasil menjadikan kawasan lingkungan tersebut tetap lestari dan bahkan menjadi salah satu hutan lindung di Indonesia. Hal ini tentu menjadi indikasi positif bagi terwujudnya perubahan iklim yang lebih baik di tengah kebingungan masyarakat akan ancaman global warming dunia.